Strength And Durability Properties Of Steel Fiber Reinforced Self Compacting Concrete (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this present study the durability characteristics of Steel fiber reinforced Self compacting concrete (SFRSCC) is determined for M30 and M40 grade concrete mixes. Along with durability strength and sorptivity is carried out and comparison is made with Plane self-compacting concrete (SCC) by chemical resistances, Initial Surface Absorption Test (ISAT).In the present study, the rational mix design procedure for self-compacting concrete is used. SCC mixes contains large quantity of powder (material whose parcel size is 0.125 mm) to maintain the plastic yield of the properties of fresh concrete as per the general guidelines for design of SCC mixes given in the EFNARC (2005). The present project consists of two phases. In the first phase, SCC mixes for different grades are developed without steel fibers and with steel fibers. The mechanical properties like compressive strength of the different grades were studied. In the second phase, based on the experimental results, durability properties were studied with the using of specimens of size 100 mm × 100 mm × 100 mm. Durability studies like Acid attack factors, Acid-Durability factors, Sulphate attack factors, Sorptivity are studied for the Plain SCC and steel Fiber Reinforced SCC and a comparison is made.